Binuclear magnesium, calcium, and zinc complexes based on nitrogen-nitrogen-coupled salicylaldiminate and ß-diketiminate ligands - Piesik, Dirk F. -J.; Stadler, Robert; Range, Sven; Harder, Sjoerd (European Journal of Inorganic Chemistry, 2009)
The diprotic bis(salicylaldimine) ligand N,N′-bis(3,5-di- tBusalicylidene)diimine, (1-NN)H, was smoothly deprotonated by reaction with two equivalents of a metal amide M[N(SiMe) ]2 (M = Mg, Ca or Zn) to form a bimetallic metal amide complex (1-NN)[MN(SiMeJ]J. This heteroleptic complex was only stable in the case of Mg and (1-NN)[MgN(SiMe)· thf] was structurally characterized by X-ray diffraction. For Ca and Zn homoleptic products could be obtained: (1-NN)Ca·(thf) and (1-NN)Zn. The latter crystallized as a trimer with approximate C -symmetry. The diprotic N-N coupled bis(β-diketimine) ligand [RHNC(Me)=C-C(Me)=N-N=C(Me)-C=C(Me)-NHR, R = 2,6-diiPr-CH ], which is abbreviated as (2-NN)H, can be deprotonated only under much harsher reaction conditions. Attempted synthesis of (2-NN)[Mg(nBu)] gave after ligand exchange the homoleptic species (2-NN)Mg and Mg(nBu), For Ca, the complexes [(2-NN)Ca] and (2-NN)[CaN(SiMe3)2· thf] both have been prepared and structurally characterized by X-ray diffraction. The latter heteroleptic complex is in benzene solution in equilibrium with [(2-NN)Ca] and Ca[N- (SiMe)]·(thf). Reaction of (2-NN)H with excess of EtZn gave the heteroleptic complex (2-NN)[ZnEt] and is stable towards ligand exchange reactions. The complex is not active in CO2/cyclohexene oxide copolymerization. © Wiley-VCH Verlag GmbH & Co. KGaA.